Study of boron neutron capture therapy components at thermal column for nuclear reactor - Safwan, Shalbi (2023)
This research study focuses on the use of barite colemanite concrete, multi-layer shielding, and collimators for boron neutron capture therapy (BNCT) components. The study aims to use barite colemanite concrete as primary shielding, implement the use of multi-layer shielding for beam shutters and beam stoppers, and optimize thermal and epithermal neutron flux while minimizing fast neutron and gamma flux using internal and external collimators. Conventional concrete as primary shielding for BNCT requires greater thickness and is less effective towards neutron and gamma radiation, thus composite concrete is used to improve shielding properties and reduce thickness. The study uses the DOE method for concrete mix and studies the effects of colemanite as fine aggregate and as filler in barite colemanite concrete mix to study effect on mechanical and shielding properties. The barite colemanite concrete testing with mechanical and shielding testing. The slump, ultra-pulse velocity, field-emission electron scanning, and compressive strength tests are used for the mechanical properties, while neutron and gamma transmission tests are used to determine shielding properties. The study found that barite colemanite concrete with 1.85% colemanite as filler, 46.95% barite, and a lower water content of 4.65% achieved mechanical strength of Grade 40, higher neutron and gamma shielding properties, and high porosity compared to conventional concrete shielding. Furthermore, based on Monte-Carlo N Particle simulation, the multi-layer shielding using barite colemanite concrete, lead, and 30% borated polyethylene for beam stoppers and beam shutters was found to be more efficient in shielding radiation compared to single-layer shielding, with more than 90% radiation absorption. The thickness of shielding was significantly reduced with the use of multi-layer shielding to less than 60 cm compared to conventional single-layer shielding. In addition, the study using Monte-Carlo N Particle simulation and measurement using rod cadmium and gold foil at 250kw reactor proposed the use of internal and external collimators to maximize thermal and epithermal neutron flux with 2 and 1.2 times higher from preliminary measurement. This research concludes that barite colemanite concrete is a suitable primary shielding material for nuclear research facilities and that the use of multi-layer shielding, and both internal and external collimators can improve the performance of BNCT components at the thermal column for nuclear reactors.